Identification of Vibrio parahaemolyticus isolates by PCR targeted to the toxR gene and detection of virulence genes - Zulkifli, Y.; Mohammed Alitheen, Noorjahan Banu; Radu, Son; Yeap, Swee Keong; Bilung, Lesley Maurice; Abdul Rahim, Raha (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Vibrio parahaemolyticus is a gram negative bacterium and causes gastrointestinal illness in humans. In this study, twenty five out of fifty cockle samples from Padang, Indonesia produced purple colonies when they were grown on selective medium, CHROMagarTM Vibrio. Specific–PCR for toxR gene detection gave positive results in which a band with 368 base pairs size appeared on the gel for all the isolates that confirmed the presence of V. parahaemolyticus. In the virulence properties test, all the isolates showed negative results for tdh and trh genes detection. The results indicate that the isolates under this study do not contain virulence properties that correlate to the ability of infection and diseases, which means that they are nonpathogenic.